Promoting children’s science, technology, engineering, and mathematics learning at home through tinkering and storytelling - Marcus, Maria; Solis, Graciela; Sellars, Shelby; Haden, Catherine A. (Frontiers in Psychology, 2023)
This study examined whether connecting storytelling and tinkering can advance early STEM (science, technology, engineering, and mathematics) learning opportunities for children. A total of 62 families with 4- to 10-year-old (M = 8.03) children were observed via Zoom. They watched a video invitation to tinker at home prepared by museum educators prior to tinkering. Then, half of the families were prompted to think up a story before tinkering (story-based tinkering group), whereas the other half were simply asked to begin tinkering (no-story group). Once they had finished tinkering, researchers elicited children’s reflections about their tinkering experience. A subset of the families (n = 45) also reminisced about their tinkering experience several weeks later. The story instructions provided before tinkering engendered children’s storytelling during tinkering and when reflecting on the experience. Children in the story-based tinkering group also talked the most about STEM both during tinkering, and subsequently when reminiscing with their parents about their tinkering experience.